A textual study of Kirigai disorders in Siddha Medicine - Miraaj, R.; Krishna, S.; Sritharan, A. (Department of Saiva Siddhantha, Faculty of Hindu Studies and Master of Saiva Siddhantha, Faculty of Advanced Studies, University of Jaffna, Sri Lanka, 2026)
The Siddha system of Medicine, one of Tamil tradition's ancient healing sciences, presents a comprehensive understanding of mental health through concepts rooted in the equilibrium of the three humors such as Vali, Azhal, and Iyyam which formed from the Panchabootham. Disturbances in this humoral balance are believed to manifest as mental disorders. Among the 4,448 diseases described by the Siddhars, 18 psychiatric conditions, collectively termed Kirigai Noi, were elaborated by Sage Agasthiyar and further clarified by Sage Yugi Munivar. The objective of this study is to systematically explore and interpret the descriptions of psychiatric disorders found in authentic Siddha texts. Data for this study were collected from classical Siddha textbooks and relevant research publications available through credible online sources. The collected information was subjected to content analysis, and sincere efforts were made to consolidate and describe traditional concepts related to Kirigai Noi. Siddha literature attributes mental illness to physiological derangements of Udal Thadukkal and disruptions in the psychological faculties as Manam, Buddhi, Sitham, and Agangaram which form part of the 96 Thathuvam. The detailed symptomatology of the 18 Kirigai Noi types demonstrates notable parallels with contemporary psychiatric conditions, including schizophrenia, mania, depression, neurotic disorders, convulsive conditions, and substance-related psychiatric disturbances. Analysis of Naadi findings, particularly the predominance of Piththa Naadi in psychiatric disorders, further supports the Siddha theoretical framework regarding mental illness. This study highlights how humoral imbalances, psychological constructs, and diagnostic pulse interpretations described in Siddha texts contribute to a holistic understanding of mental disorders. Overall, the exploration underscores the depth of Siddha psychiatric knowledge and its potential relevance to integrative mental health approaches. By aligning classical descriptions with modern psychiatric perspectives, this study demonstrates how Siddha insights may complement contemporary mental health practices and provide a broader framework for understanding and managing psychiatric conditions.
Keywords: Kirigai Noi; Naadi; Udal thadukkal; Three humours; Panchabootham